Auditory attention in autism spectrum disorder: An exploration of volumetric magnetic resonance imaging findings. Issue 5 (28th May 2018) - Lalani, Sanam J.; Duffield, Tyler C.; Trontel, Haley G.; Bigler, Erin D.; Abildskov, Tracy J.; Froehlich, Alyson; Prigge, Molly B. D.; Travers, Brittany G.; Anderson, Jeffrey S.; Zielinski, Brandon A.; Alexander, Andrew; Lange, Nicholas; et al.
ABSTRACT: Studies have shown that individuals with autism spectrum disorder (ASD) tend to perform significantly below typically developing individuals on standardized measures of attention, even when controlling for IQ. The current study sought to examine within ASD whether anatomical correlates of attention performance differed between those with average to above-average IQ (AIQ group) and those with low-average to borderline ability (LIQ group) as well as in comparison to typically developing controls (TDC). Using automated volumetric analyses, we examined regional volume of classic attention areas including the superior frontal gyrus, anterior cingulate cortex, and precuneus in ASD AIQ ( n  = 38) and LIQ ( n  = 18) individuals along with 30 TDC. Auditory attention performance was assessed using subtests of the Test of Memory and Learning (TOMAL) compared among the groups and then correlated with regional brain volumes. Analyses revealed group differences in attention. The three groups did not differ significantly on any auditory attention-related brain volumes; however, trends toward significant size–attention function interactions were observed. Negative correlations were found between the volume of the precuneus and auditory attention performance for the AIQ ASD group, indicating larger volume related to poorer performance. Implications for general attention functioning and dysfunctional neural connectivity in ASD are discussed.